LEGAL ASPECTS OF PUBLIC ADMINISTRATION IN THE SPHERE OF USE AND PROTECTION OF LANDS OF DEFENSE (Journal of actual problems of jurisprudence, 2019)
In given clause the features of state management in sphere of protection and use of grounds of a defense are investigated, thathas allowed the author to formulate the offers on perfection of the current legislation РК.